2011
DOI: 10.1002/ppul.21455
|View full text |Cite
|
Sign up to set email alerts
|

Infant formula alters surfactant protein A (SP‐A) and SP‐B expression in pulmonary epithelial cells

Abstract: Surfactant proteins A (SP-A) and SP-B are critical in the ability of pulmonary surfactant to reduce alveolar surface tension and provide innate immunity. Aspiration of infant milk formula can lead to lung dysfunction, but direct effects of aspirated formula on surfactant protein expression in pulmonary cells have not been described. The hypothesis that infant formula alters surfactant protein homeostasis was tested in vitro by assessing surfactant protein gene expression in cultured pulmonary epithelial cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This includes the intestine, in which differential allele-specific expression of SP-A has been observed (12,13). We previously reported that SP-A expression is reduced in a human bronchiolar cell line (H441) upon transient exposure to infant formula (37). Based on those results and the fact that this model of neonatal NEC requires formula feeding, we postulated that a reduction in intestinal levels of SP-A may play a role in the development of NEC in our experimental rat model.…”
Section: Intestinal Levels Of Sp-a Were Not Significantly Altered In ...mentioning
confidence: 99%
“…This includes the intestine, in which differential allele-specific expression of SP-A has been observed (12,13). We previously reported that SP-A expression is reduced in a human bronchiolar cell line (H441) upon transient exposure to infant formula (37). Based on those results and the fact that this model of neonatal NEC requires formula feeding, we postulated that a reduction in intestinal levels of SP-A may play a role in the development of NEC in our experimental rat model.…”
Section: Intestinal Levels Of Sp-a Were Not Significantly Altered In ...mentioning
confidence: 99%
“…Pulmonary surfactant is crucial in the reduction of the surface tension at the air-water interface where pulmonary surfactant is degraded and recycled. SP-B is an important pulmonary surfactant-associated protein capable of reducing or altering the surface tension by changing the surface area, preventing alveolar collapse ( 1 3 ). Studies have shown SP-B protein deficiency to be associated with the pathogenesis of neonatal respiratory distress syndrome (RDS) ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%